Pendidikan Karakter Sebagai Landasan Pembentukan Generasi Muda - Fadhillah Quratul ‘Aini; Rahmi Yuli Andini Hasibuan; Gusmaneli Gusmaneli (Universitas 45 Surabaya, 2024)
Character education is an important pillar in the formation of a quality young generation. This paper describes the urgency of character education in forming individuals who are not only intellectually intelligent, but also have strong moral values. Through a literature review and data analysis, this paper shows that character education can form a young generation who has integrity, empathy, responsibility, and the ability to coexist harmoniously in a diverse society. Apart from that, this paper also identifies challenges and solutions in implementing character education in various educational contexts. Keywords : ,